(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A clinical facility that offers treatment for chronically sick patients is the Intensive Care Unit. The stay will affect patient recovery both in the short and long run. The nurses are well placed to take effective measures to restore ICU globally Patients A critical way of evaluating service is the monitoring of the clinical condition of patients released from intensive care units. The objective of this research was to evaluate patients’ physical and mental wellbeing shortly after ICU discharge 24 hours after discharge. This research was concerned with the concept of transition, Intensive Care Unit Transition of Patients (ICU), Patient discharge from intensive care, impact on patient transfer, Coordination of the intensive care unit with the wards, Patient and families in the Intensive Care Unit (ICU) ICU Transition Post-ICU trips, ICU Transfer Post-ICU Transfer Post-ICU Physical Incidence. Temporary treatment, Role of the health care provider